2019
DOI: 10.3389/fpsyg.2019.01665
|View full text |Cite
|
Sign up to set email alerts
|

Imaginary Companions, Inner Speech, and Auditory Verbal Hallucinations: What Are the Relations?

Abstract: Interacting with imaginary companions (ICs) is now considered a natural part of childhood for many children, and has been associated with a range of positive developmental outcomes. Recent research has explored how the phenomenon of ICs in childhood and adulthood relates to the more unusual experience of hearing voices (or auditory verbal hallucinations, AVH). Specifically, parallels have been drawn between the varied phenomenology of the two kinds of experience, including the issues of quasi-perceptual vividn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
1
28
1
Order By: Relevance
“…Specifically, there is evidence to suggest that having an IC as a child is associated with both elevated hallucination-proneness and bias in auditory signal detection skills as an adult (Fernyhough et al, 2019). In addition, children with ICs are more likely to hear words amidst jumbled speech, which is similar in many ways to effects seen for SWS (Fernyhough et al, 2007).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Specifically, there is evidence to suggest that having an IC as a child is associated with both elevated hallucination-proneness and bias in auditory signal detection skills as an adult (Fernyhough et al, 2019). In addition, children with ICs are more likely to hear words amidst jumbled speech, which is similar in many ways to effects seen for SWS (Fernyhough et al, 2007).…”
Section: Resultsmentioning
confidence: 93%
“…This suggested that d' change and hallucination-proneness were nevertheless unrelated, despite the effect of IC status. (Fernyhough et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations